Gut microbiota-bile acid crosstalk contributes to the rebound weight gain after calorie restriction in mice - Li, Mengci; Wang, Shouli; Li, Yitao; Zhao, Mingliang; Kuang, Junliang; Liang, Dandan; Wang, Jieyi; Wei, Meilin; Rajani, Cynthia; Ma, Xinran; Tang, Yajun; Ren, Zhenxing; et al. (Nature communications, 2022)
Calorie restriction (CR) and fasting are common approaches to weight reduction, but the maintenance is difficult after resuming food consumption. Meanwhile, the gut microbiome associated with energy harvest alters dramatically in response to nutrient deprivation. Here, we reported that CR and high-fat diet (HFD) both remodeled the gut microbiota with similar microbial composition, Parabacteroides distasonis was most significantly decreased after CR or HFD. CR altered microbiota and reprogramed metabolism, resulting in a distinct serum bile acid profile characterized by depleting the proportion of non-12α-hydroxylated bile acids, ursodeoxycholic acid and lithocholic acid. Downregulation of UCP1 expression in brown adipose tissue and decreased serum GLP-1 were observed in the weight-rebound mice. Moreover, treatment with Parabacteroides distasonis or non-12α-hydroxylated bile acids ameliorated weight regain via increased thermogenesis. Our results highlighted the gut microbiota-bile acid crosstalk in rebound weight gain and Parabacteroides distasonis as a potential probiotic to prevent rapid post-CR weight gain. Caloric restriction is a common approach to weight reduction, however, weight regain is common. Here the authors report that caloric restriction reduces the abundance of Parabacteroides distasonis in the gut and alters serum bile acid (BA) profile, which contribute to weight regain in mice.